Wildlife Conservation through Local Community Engagement in India - Kalra, Sharda; Poonia, Asha; Sharma, Radhika; Kaur, Ramneek; Sharma, Parvati; Kumar, Amit; Gulia, Nisha (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Illegal wildlife trade is flourishing due to the enhancement and infusion phenomenon which not only led to survival but also thriving of such clandestine trade. Most of the illicit wildlife crimes (wildlife capturing, hunting and their trafficking) remain unrevealed because of unawareness or incognizance and authoritative phenomenon fragility. Apart from the above reasons, other reasons like poverty, illiteracy and unemployment play the role of key factors to drive and promote undesirable involvement of local communities in wildlife trade. The major share of profit of such business goes to the intermediaries who are generally high level traders while local communities are most adversely affected. For local communities, this is the only source of livelihood where community members act as sub-dealers to supply the wildlife and their products to the racketeers/high level traders. In India, most widespread threats to wildlife diversity is the poaching by local community for (1)their consumption, (2) financial benefits, and (3) non-financial benefits including socio−cultural rituals, (4) retaliation either due to wildlife depredation or traditional practice of hunting animals and birds. Effective implementation of Wildlife legislations and alternative livelihood to prohibit the illegal activity and engagement of local community in conservation programme.